The India option: perceptions of Indian software solutions. (1st January 1998) - Abraham, Thomas; Ahlawat, Sucheta; Ahlawat, Sunita
A survey of US software developers has been conducted to determine how Indian software is perceived in terms of quality and productivity and to determine if, in fact, many MIS managers view it as a viable option. We find that Indian software solutions (ISS) are an option for many US firms. However, the growth in offshore sourcing is not expected to increase at the rapid rates of the past. There are several reasons for this. First, the Indian software industry has not matured to the level of offering a variety of services including off-the-shelf packages. Bodyshopping/personnel remains the main attraction, although the industry has made strides in offering customised software. Second, the range of user experiences with ISS varies considerably. Those using the bodyshopping option have significantly better experiences than those using the customised software option. This has implications for how users perceive the quality of ISS products and Indian programmers, and whether they want to commission ISS in the future. Third, a lack of infrastructure support is cited as the most negative aspect of doing business with India. Infrastructure problems include power cuts, traffic, and the need for modern international airports.